An Energy Efficient Cloud-Based Routing Protocol for Wireless Sensor Network (WSN) for Improving Throughput and Packet Delivery Ratio - S., Vishwas; K., Hareesh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study explores the integration of wireless sensor networks with cloud platforms to address inherent limitations, including processing, storage, and power constraints. Researchers leverage the specific requirements of Wireless Sensor Networks (WSN) to propose innovative solutions, particularly focusing on energy efficiency and minimizing delays in surveillance applications. The data collected from these applications undergo streamlined processing and analysis in a cloud database. To ensure efficient and reliable transmission from the WSN to the cloud server, a comprehensive Secured Energy Efficient Framework (SEEF) is introduced. SEEF incorporates cluster-based topology, Content Slot Allocation based Multi-Layer MAC (CSA-ML MAC) protocol, and a trust-based Sybil attack detection mechanism. CSA-ML MAC dynamically allocates variable-sized slots, achieving notable improvements in end-to-end delay, duty cycle, and packet delivery ratio. The Sybil attack detection mechanism enhances accuracy, leading to reduced false positives and improved true positives. The routing protocol optimizes intra-cluster and inter-cluster phases, utilizing a flower pollination algorithm to enhance inter-cluster routing. Collectively, these proposed mechanisms contribute to energy savings, reduced delay, and improved overall performance compared to existing protocols.